1998
DOI: 10.1002/he.10108
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Enculturation: Collegiality, Mentoring, and Structure

Abstract: American doctoral programs remain the premier training ground for the w o r l d ' s future scientists and scholars (Clark, 1995). Every year, thousands of students enter graduate school with hopes of bright careers; many aspire t o w a rd careers as professors and scientists (Boyle, 1996). All of these p rospective scholars must begin as first-year graduate students. These students go through a cultural learn i n g or enculturation process in which they l e a rn to act as productive members of their graduate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 18 publications
2
58
0
Order By: Relevance
“…With respect to program-level factors, the size of a department housing the program, proportion of female students, and mean GRE quantitative score were statistically significantly associated with the timing of doctorate attainment. A decrease in the size of the department housing the program was associated with a statistically significant increase in the odds of doctorate attainment in the program, a finding that agrees with the literature indicating that smaller departments are associated with shorter TTD (Bauer 2004;Boyle & Boice, 1998;Dinham & Scott, 1999;Ferrer de Valero, 2001). The higher the proportion of female students or the mean GRE quantitative score, the higher the odds of doctorate attainment in any given year in the program, other factors held constant.…”
Section: Quantitative Phasesupporting
confidence: 82%
“…With respect to program-level factors, the size of a department housing the program, proportion of female students, and mean GRE quantitative score were statistically significantly associated with the timing of doctorate attainment. A decrease in the size of the department housing the program was associated with a statistically significant increase in the odds of doctorate attainment in the program, a finding that agrees with the literature indicating that smaller departments are associated with shorter TTD (Bauer 2004;Boyle & Boice, 1998;Dinham & Scott, 1999;Ferrer de Valero, 2001). The higher the proportion of female students or the mean GRE quantitative score, the higher the odds of doctorate attainment in any given year in the program, other factors held constant.…”
Section: Quantitative Phasesupporting
confidence: 82%
“…They all emphasize the aspect of personalized advice, relationship. Going one step ahead Friendship (Kram, 1985) and honest self-disclosure (Boyle & Boice, 1998;Johnson, 2003) have been identified as significant mentor functions. As a matter of fact, all these things are the practices that are involved right from the beginning of the doctoral program, at all levels of the research work.…”
Section: Discussionmentioning
confidence: 99%
“…As Ferreira (2003) and Hirt and Muffo (1998) note, each university department establishes its own recruitment and admission policies, curriculum, performance criteria, and expectations for how students should spend their time and talent. The extant research on departmental climate has identified several issues related to student socialization and decisions to persist or leave, including the availability of explicit information about program expectations, the use of preliminary and qualifying exams which provide feedback to students early in their programs, opportunities to engage in research early in graduate training, opportunities for diverse skill development to strengthen post-graduation career success, and the propensity for students to work in isolation (Boyle & Boice, 1998;Earl-Novell, 2006;Gardener, 2009b;Golde, 2005;Golde & Dore, 2001;Hirt & Muffo, 1998;Solem & Schlemper, 2009). In addition to establishing policies and practices that influence doctoral student success, "feeling cared about and appreciated at the departmental" level can also serve as a buffer to emotional exhaustion for graduate students and is connected to successful completion (Hunter & Devine, 2016, p. 52).…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%